Adapting the Trait Emotional Intelligence Questionnaire Short Form (TEIQUE-SF) into Indonesian Language and Culture Using Confirmatory Factor Analysis - Silvia Kristanti Tri Febriana (Journal of Educational, Health and Community Psychology, 2021)
This study aimed to adapt the TEIQue-SF 1.50 measuring instrument to the Indonesian culture. This research was conducted in two studies. In Study 1, the translation process and the equivalence testing were carried out, involving six translators, three expert reviewers, and ten laypeople for cognitive debriefing. Study 2 involved 200 subjects who were workers in Indonesia and tested the TEIQue-SF 1.50 measuring instrument with confirmatory factor analysis using AMOS version 22. The entire adaptation process referred to the International Test Commission (ITC) Guidelines for Test Adaptation 2016. The CFA results showed that the TEIQUE-SF 1.50 measurement model was fit to the one-factor model. Overall, this study showed that the Indonesian version of TEIQue-SF 1.50 was valid and reliable so that it can be used to measure the Trait Emotional Intelligence in Indonesia